STORYTELLING AS A COMMUNICATION STRATEGY MARKETING ON INSTAGRAM: STUDY THE TUKU SAMBAL CASE - Yosi Fahdillah; irfan Hassandi; Yossinomita; Wahya Lubis (Journal of Business Studies and Management Review, 2025)
This Research This aiming For analyze how storytelling is used as a communication strategy marketing by UMKM Tuku Sambal through the Instagram platform. Using approach qualitative with method studies case , research This explore practice narrative built by the Instagram account @tukusambal in convey message brand , build connection with consumers , and strengthen identity brand . Analysis done with to study content uploads (captions, visuals, interactions) users ) and reflect it through Narrative Paradigm theory , Social Media Marketing, Brand Identity, and Integrated Marketing Communication (IMC). Research results show that the storytelling applied by Tuku Sambal is authentic , consistent and contains values relevant culture​ with life audience . The story being told No only introduce products , but also build proximity emotional and strengthening loyalty customers . This strategy is also supported by uniform visual branding , style down to earth language , as well as interaction two active direction​ through social media . Findings This to emphasize that storytelling is not only tool communication creative , but also an effective marketing strategy in build identity brand and improve involvement customer digitally .